Hollywood Ascendant: American Films in Hungary in the 1970s - Takács, Róbert (Hungarian Journal of English and American Studies, 2021)
Hungarian cultural policy makers denied Hungarian viewers access to American films between 1949 and 1956. Hollywood movies were publicly shown again behind the Iron Curtain from 1957 in spite of hostile American–Hungarian bilateral relations after the crushing of the Revolution of 1956. The de-Stalinized cultural policy of Hungary allowed for one third of the films released in Hungarian cinemas to come from capitalist countries. In the 1970s the United States became the largest non-socialist film exporter to Hungary and Hollywood export “sky-rocketed” at the end of the decade. The annual purchase of thirteen to twenty-nine American films still made it possible to apply ideological filters; however, only a part of the films released in Hungary could be regarded as useful in representing negative social trends in the United States. The majority of Hollywood movies screened in Hungary should rather be labeled as entertaining, and these served leisure on one hand and financial considerations on the other. Entertainment was recognized as a legitimate demand of the public after 1956 and the program of the cinemas had to be supplemented from Western sources. In the 1970s Hollywood became the number one Western movie entertainer in communist Hungary. The narrowing budgetary sources of cultural policy and the need for self-financing also paved the way for this tendency. (RT)